Efecto insectistático de extractos etanólicos de clavo y pimienta en Trialeurodes vaporariorum West. (Hemiptera: Aleyrodidae) - Aguilar-Astudillo, Eduardo; Rodríguez-Hernández, Cesáreo; Bravo-Mojica, Hiram; Soto-Hernández, R. Marcos; Bautista-Martínez, Néstor; Guevara-Hernández, Francisco (Instituto de Ecología, A.C., 2019)
In the management the greenhouse whitefly, Trialeurodes vaporariorum, organosynthetic pesticides are commonly used, increasing the frequency and doses of application, thus generating resistance of the pest to pesticides and eliminating natural enemies. Then, this make necessary to search for alternatives that contribute to solve the whitefly problem without deteriorating the environment at must. Among several options, bioassays were established applying ethanol extracts of clove Syzygium aromaticum and pepper Pimenta dioica to the leaves of tomato plants where 2-day-old adults were released in a bioassay, and on another set of tomato plants oviposition was previously induced for 3 d. Mortality of adults and laid eggs, as well as hatched eggs were recorded. The 1.0% clove extracts caused 33.7 adult mortality, 72.9% oviposition inhibition with CIO50 of 0.19, and pepper extracts caused 32.5% adult mortality, 65.8% oviposition inhibition with CIO50´s of 0.46%, and both inhibited from 52.6 to 100% hatching with CIE50´s from 0.11 to 0.71% respectively, it being total when 1.0% pepper extract is applied to 2-day-old eggs. It is suggested that activity of the clove and pepper ethanol extracts is mainly insectistatic, although it can have an ovicide effect, it is a biorational input to be integrated into the ecological management of the greenhouse whitefly.